Insights into CoFe2O4/Peracetic Acid Catalytic Oxidation Process for Iopamidol Degradation: Performance, Mechanisms, and I-DBP Formation Control - Haiwei Wu; Jiaming Zhang; Fangbo Zhao; Wei Fan; Song Yang; Jun Ma (Nanomaterials)
In chlorination disinfection treatment, residual iodinated X-ray contrast media (ICMs) are the precursors to iodinated disinfection by-products (I-DBPs). This study employed CoFe2O4 nanoparticle catalytic peracetic acid oxidation (CoFe2O4/PAA) to remove iopamidol (IPM) and control I-DBP formation. The experimental results demonstrated that over 90% of the IPM degradation was achieved in 40 min. The metastable intermediate (≡Co(II)-OO(O)CCH3), rather than the alkoxyl radicals, was identified as the dominant oxidation species (ROS). The electron transfer pathways between the metastable intermediate and IPM were oxygen-atom transfer and single-electron transfer. The monoiodoacetic acid formation potential (MIAAFP) was investigated. In ultraviolet-activated ClO− (UV/chlorine), a portion of I− generated through IPM dehalogenation underwent conversion to reactive iodine species (RIS), consequently elevating the MIAAFP. In CoFe2O4/PAA, the MIAAFP was less than 43% of that in UV/chlorine, which can be attributed to the complete conversion of I− into iodate IO3− without generating RIS. CoFe2O4/PAA is thus a promising treatment for removing ICMs and controlling I-DBP formation due to the efficient degradation of ICMs while avoiding the generation of RIS.